(untitled) (Innovative professional education, 2024)
Considered psychological assistance in institutions of professional (vocational and technical) education from the point of view of the ecosystem approach. The purpose, task, content, and structure of the all-Ukrainian project «Ecosystem of psychological assistance in the field of education» are specified. Peculiarities of the ecosystem of psychological assistance in institutions of professional (vocational and technical) education are highlighted. The mental health problems of participants in the educational process of professional (vocational and technical) education institutions in the modern conditions of a military society are analyzed.